Acceptance and Online Interpretation of “Gender-Neutral Pronouns”: Performance Asymmetry by Chinese English as a Foreign Language Learners - Ma, Zheng; Wu, Shiyu; Xu, Shiying (Frontiers in Psychology, 2022)
The present study (N = 109) set out to examine the role of cross-linguistic differences as a source of potential difficulty in the acceptance and online interpretation of the English singular they by Chinese English as a Foreign Language (EFL) learners across two levels of second-language proficiency. Experiment 1 operationalized performance through an untimed acceptability judgment test and Experiment 2 through a self-paced reading task. Statistical analyses yielded an asymmetric pattern of results. Experiment 1 indicated that unlike native English speakers who generally accepted the singular they with all antecedent types, two Chinese EFL groups consisting of English majors (higher level) and non-English majors (lower level) both rated it as the least acceptable pronoun regardless of their proficiency level. In contrast, Experiment 2 demonstrated that like native English speakers, both Chinese EFL groups were not disrupted in their reading by the use of the singular they most of the time, although its online interpretation was modulated by L2 proficiency levels of the participants. While the English majors were not affected by the use of the singular they, the non-English majors spent a significantly longer time reading the latter region of the sentences where the singular they was used. In short, the results of the two experiments seem to indicate that under no time constraint, L2 speakers showed a heightened degree of grammar sensitivity, whereas when there was a time constraint, their grammatical sensitivity was reduced by a greater need to focus on meaning. The difficulty for Chinese EFL learners to acquire the singular they may be located at the restructuring of their existing knowledge of the plural feature of they [−PLURAL] in their mental lexicon and the adaptation to the sociocultural norms of the target language. The pedagogical implications of the findings are discussed.